RANCANG BANGUN SISTEM INFORMASI PARIWISATA DI KABUPATEN LOMBOK TIMUR BERBASIS ANDROID - Arsyani, Imam Hidayat; Setiyaningsih, Wiji (Department of System Information, 2024)
East Lombok Regency is one of eight regencies in West Nusa Tenggara Province that has many tourist attractions. However, tourist attractions in East Lombok Regency itself are currently still poorly informed by the outside community in particular due to the lack of information. Therefore, tourism in East Lombok Regency requires promotional facilities so that both local and outside communities can easily find out tourism information. The design of a tourism information system in East Lombok Regency by utilizing the internet will make it very easy to find information about tourism in East Lombok Regency and is expected to be very capable of being a means of tourism promotion. The design of this tourism information system uses a user centered design model.